Factors affecting the first-year students’ learning English in a blended learning program at a university in Vietnam - Phạm Thị Thùy Ninh
Thesis presented literature review: Blended learning, factors affecting student's learning english in a blended learning method. Research methodology: research design, data collection methods and instruments, data collection procedure, data analysis. Findings and discussion.